Fikih Konsep Dasar Pendidikan Islam - Sholihin, Choirus (STID Raudlatul Iman Sumenep, 2017)
Education is one of the most essential keys in human life. Both the bad human resources depend on the education gained. Education of an investment in human resources. If the education obtained by a person has a quality that mampuni, then both also human resources owned. Therefore, the educational design should be well prepared so that the results achieved are satisfactory. Making quality human resources an important role of educational institutions. The educational institution is an institution that manages the teaching and learning activities and in essence mobilizes the learners to have the desire to learn, thus obtaining various insights on knowledge, skills, skills and gaining knowledge of the cognitive, affective and psychomotor patterns he / she acquires in learning. The ability of learners to acquire knowledge, skills and expertise in terms of ability in cognitive, affective and psychomorik has a level of ability that is not the same. Therefore, in thinking and to move in the world of education must design perfectly. The success and formation of an educational world that will produce perfect output, becomes the role of an educator or teacher, thus, looking at the magnitude of educational or teacher duties, al-Imam Abi Hamid Muhammad ibn Muhammad al-Ghazali suggests to always hold on and strengthen the eight basic classical concepts educators.